Comparison of the kappa-opioid receptor antagonist DIPPA in tests of anxiety-like behavior between Wistar Kyoto and Sprague Dawley rats - Carr, Gregory V. (2010)
RATIONALE: Recent evidence suggests a role for the dynorphin/ kappa-opioid receptor (KOR) system in the expression of stress-induced behaviors. Wistar Kyoto (WKY) rats exhibit increased depression-like and anxiety-like responses in behavioral tests compared to other strains and may be a model of comorbid depression and anxiety characterized by increased activity within the dynorphin/KOR system. Though KOR antagonists produce antidepressant-like effects in WKY rats, their effects in tests of anxiety-like behavior have not been examined in the WKY strain. OBJECTIVE: The aim of the current study was to investigate the effects of the KOR antagonist 2-(3,4-dichlorophenyl)-N-methyl-N-[(1S)-1-(3-isothiocyanatophenyl)-2-(1-pyrrolidinyl) ethyl]acetamide hydrochloride (DIPPA) on the behavior of WKY rats and Sprague Dawley (SD) rats in tests of anxiety-like behavior. METHODS: The novelty-induced hypophagia and defensive burying tests were used to measure anxiety-like behavior in WKY and SD rats and determine the effects of DIPPA on anxiety-like behavior in both strains. RESULTS: WKY rats displayed greater amounts of anxiety-like behavior compared to SD rats. DIPPA produced anxiolytic-like effects in both tests in both strains. CONCLUSIONS: WKY rats display more anxiety-like behavior at baseline compared to SD rats, and DIPPA produced anxiolytic-like effects in both WKY and SD rats. These findings support previous research suggesting that KOR antagonists possess anxiolytic-like properties and may potentially represent a novel class of treatments for mood disorders.